The training and development needs of nurses in Indonesia: paper 3 of 3 - Hilan Aflah; Hicks Carolyn; Hennessy Deborah; Kawonal Yoanna (BMC, 2006)
Abstract Background Indonesia's recent economic and political history has left a legacy of widespread poverty and serious health problems, and has contributed to marked inequalities in health care. One means of responding to these challenges has been through a reconsideration of the professional roles of nurses, to enable them to deal with the range and complexity of health problems. However, there are currently a number of obstacles to achieving these aims: there is a serious shortfall in trained nurses; the majority of nurses have only limited education and preparation for the role; and there is no central registration of nurses, which means that it is impossible to regulate either the profession or the standards of care. This study aimed to establish the occupational profiles of each grade of nurse, identify their training and development needs and ascertain whether any differences existed between nurses working in different regions or within hospital or community settings. Methods An established and psychometrically valid questionnaire was administered to 524 nurses, covering three grades and coming from five provinces. Results Significant differences in job profile were found in nurses from different provinces, suggesting that the nature of the role is determined to some degree by the geographical location of practice. The roles of hospital and community nurses, and the different grades of nurse, were fairly similar. All nurses reported significant training needs for all 40 tasks, although these did not vary greatly between grade of nurse. The training needs of nurses from each of the provinces were quite distinct, while those of hospital nurses were greater than those of community nurses. Conclusion The results suggest that the role of the nurse is not as diverse as might be expected, given the different levels of preparation and training and the diversity of their work environments. This may reflect the lack of a central registration system and quality framework, which would normally regulate clinical activities according to qualifications. The differences in training needs between subsections of the sample highlight the importance of identifying skills deficits and using this information to develop customized post-registration education programmes. Together, these results provide a rigorous and reliable approach to defining the occupational roles and continuing education needs of Indonesian nurses.